Novel double layer lanthanide metal–organic networks for sensing applications. Issue 2 (11th December 2017) - Wang, Jun; Zhang, Qiang-Sheng; Dou, Wei; Kirillov, Alexander M.; Liu, Wei-Sheng; Xu, Cong; Xu, Cai-Ling; Fang, Ran; Yang, Li-Zi
Abstract : Two isostructural lanthanide-based 2D coordination polymers were synthesized under hydrothermal conditions and fully characterized. The obtained compounds display notable sensing ability for p -phenylenediamine, benzidine, and acetone analytes. Abstract : A trifunctional aromatic building block (H2 L) containing three different types of functional groups (carboxyl C(O)OH, aldehyde C(O)H, and O-ether) was applied for the hydrothermal synthesis of two novel lanthanide 2D coordination polymers [Ln(μ-HL)(μ3 -L)(phen)] n {Ln = Tb (1 ) and Eu (2 ); H2 L = 5-methoxy-(4-benzaldehyde)-1, 3-benzene dicarboxylic acid; phen = 1, 10-phenanthroline}. Both compounds1 and2 are isostructural and reveal very complicated 2D metal–organic double layers with the3, 4L27 topology. The presence of free aldehyde groups positioned outside of the double layers opens up a possibility of using them as functional groups toward sensing amines and small organic molecules. The fluorescence measurements for the Tb derivative1 reveal that it acts as an efficient fluorescence sensor for p -phenylenediamine, benzidine and acetone molecules via a luminescence quenching effect. A similar sensing behavior was observed for the Eu compound2 . Moreover, thin-films of1-PEG on glass (1-PEG-glass thin-film material) were fabricated and investigated for the detection of amine vapors.